Coenzyme Q10 protects against β‐cell toxicity induced by pravastatin treatment of hypercholesterolemia. Issue 7 (7th December 2018) - Lorza‐Gil, Estela; de Souza, Jane C.; García‐Arévalo, Marta; Vettorazzi, Jean F.; Marques, Ana Carolina; Salerno, Alessandro G.; Trigo, Jose Roberto; Oliveira, Helena C. F.
Abstract: New onset of diabetes is associated with the use of statins. We have recently demonstrated that pravastatin‐treated hypercholesterolemic LDL receptor knockout (LDLr −/− ) mice exhibit reductions in insulin secretion and increased islet cell death and oxidative stress. Here, we hypothesized that these diabetogenic effects of pravastatin could be counteracted by treatment with the antioxidant coenzyme Q 10 (CoQ 10 ), an intermediate generated in the cholesterol synthesis pathway. LDLr −/− mice were treated with pravastatin and/or CoQ 10 for 2 months. Pravastatin treatment resulted in a 75% decrease of liver CoQ 10 content. Dietary CoQ 10 supplementation of pravastatin‐treated mice reversed fasting hyperglycemia, improved glucose tolerance (20%) and insulin sensitivity (>2‐fold), and fully restored islet glucose‐stimulated insulin secretion impaired by pravastatin (40%). Pravastatin had no effect on insulin secretion of wild‐type mice. In vitro, insulin‐secreting INS1E cells cotreated with CoQ 10 were protected from cell death and oxidative stress induced by pravastatin. Simvastatin and atorvastatin were more potent in inducing dose‐dependent INS1E cell death (10–15‐fold), which were also attenuated by CoQ 10 cotreatment. Together, these results demonstrate that statins impair β‐cell redox balance, function and viability. However, CoQ 10 supplementation can protect the statins detrimental effects on the endocrine pancreas. Abstract : Statins impair β‐cell redox balance, function, and viability. CoQ10 supplementation can protect the statins detrimental effects on the endocrine pancreas.